Experiência do uso de aplicativo m-Health em pacientes com hipertensão - Locatelli, Jakeline Karla (2021)
Low adherence to treatment for hypertension remains a serious public health problem and a change in behavior can help adherence to treatment. In this scenario, m-Health applications accept an increasing number of users, motivated by the possibility of monitoring their health conditions. However, user engagement in the use of these applications is still a challenge, which encourages the study of techniques that can be combined to promote a satisfactory experience and, consequently, expand the use of technology over time. Given the context, this dissertation aimed to understand the long -term experience of patients with hypertension using the m-Health app. This is a qualitative, exploratory study, which was conducted with the same qualified individuals who participated in the experimental group in the non -randomized, controlled clinical trial carried out in 2019. 36 patients with hypertension registered in the Unified Health System participated in the experiment al group. Health in the municipality of Passo Fundo, which used the eEstilo de Vida application for a period of three months. As a variable, the user experience (UX) when using the application is analyzed. After transcribing the recorded identified, qualitative data were categorized into satisfactory, unsatisfactory, user inability, lack of engagement, lack of follow-up, technical aspect, usability, functionality, new features, improving usability and technical support. The results of the study showed that, after one year, there was no user engagement in the use of the m-Health application. Among the factors that contributed to a lack of engagement are user inability, a lack of follow-up and technical issues. Knowing the user is essential when proposing a health with health intervention, as expectations and needs are related to a satisfactory UX, which leads to engagement. In addition, it is necessary to evaluate the effectiveness of combined techniques, including those proposed by TCC.